A key to the species of Protogamasellus (Acari: Ascidae), with a new species from the Brazilian Pantanal - Yamada, Mariana; de Moraes, Gilberto J. (Zootaxa, 2020)
A study of soil mites in the Brazilian Pantanal, southwestern Brazil, has shown the frequent occurrence of the genus Protogamasellus, especially in cultivated land. Three species were found in this study, Protogamasellus mica (Athias-Henriot), Protogamasellus sigillophorus Mineiro, Lindquist & Moraes, and a new species, Protogamasellus pantanal n. sp., which is here described. A taxonomic key for the identification of species of the genus was prepared, based on the examination of the type specimens of the new species here described, of specimens of other species found in Brazil in this and previous studies, and on the information found in the literature for other species.